Representações sociais e lesbianidade: conversações acerca dos direitos sexuais e reprodutivos - Quartiero, Gabriela (2022)
This research aims to analyze how the sexual and reproductive rights of lesbians are experienced. Specifically, we had as specific objectives: to observe how certain social representations produce meaning and practices in the daily life of lesbians; to know the daily practices of lesbians in their relationships with their own bodies,sexuality and desire; to identify tactics of (self)care related to reproductive health, paying attention to methods of contraception; and to understand how the construction of lesbian communities contributes in the resistances to lesbophobia, against machismo and sexism. We used a methodological triangulation that corresponds to conducting focus groups with self-declared lesbian subjects, applying a sociodemographic questionnaire and the Free Word Association Technique. Throughout the course of the focus groups, we used the field diary. The analysis and interpretations are located in the area of Social Psychology, with interlocution from Feminist Studies and Kleinian psychoanalysis, with an aim to contributing to the construction of knowledge in a critical social psychology, to the representational processes and to the Sexual and Reproductive Rights. As results, it was noted that the social representations of gender, the feminist movement, motherhood were important issues discussed. The field of affectivity gained prominence during contact with the interlocutors, especially the feelings of fear and loneliness. We conclude that from the perspective ofsocial representations, there seems to be a hardship in the transformation of family and social relationships. The force of compulsory heterosexuality makes the main survival tactic for lesbians to retreat into solitude, alone or with their respective partners.